Infraestrutura econômica, incerteza e investimento privado - Jefferson Souza Fraga (2019)
This study aims to develop and demonstrate the thesis that sharp cuts in investment in infrastructure and their continued physical deterioration reduce the elasticity of aggregate private investment in relation to its determinants, such as real interest rates, credit, real exchange rates and public investment. The deterioration of an economy's infrastructure influences the agents' perceptions, in particular of entrepreneurs, that the level of infrastructure and its related services is of accentuated insufficiency, can stimulate a convention (shared belief), which will determine the expectations of the agents, affecting private investment and, also, its sensitivity to its determinants. Initially, the post-Keynesian theory related to private investment is recovered, presenting the interactions between public investment in economic infrastructure and private investment, as well as its impacts on the whole economy. The empirical model underlying this thesis is developed according to the model of the flexible accelerator, and reformulated to capture the effects of infrastructure and other factors that affect the accumulation of private capital. For this, two data series and country samples were used. The Panel Time Series approach is used to estimate the private investment function that relates private capital stock to infrastructure. Dummy variables are inserted into the regression structure to capture changes in the elasticities of private investment in relation to their determinants. The first econometric exercise is conducted for the period 1985-2013 for six Latin American economies (Argentina, Brazil, Chile, Colombia, Mexico and Peru). The series of infrastructure is composed of: public and private investment in water and sanitation, in energy, telecommunications and transport, all are in relation to GDP. A synthetic measure of infrastructure taken from principal component analysis (PCA) - composed of: total length of paved roads and length of the railway in kilometers, aerial departures registered in the world of registered carriers in the country, fixed telephone subscriptions, capacity of electricity generation, in Gigawatt, and loss of transmission and distribution of electricity - is employed in a second exercise for the period 1985-2013 to eighty-seven economies. The empirical tests corroborate the main hypotheses of this thesis and indicate the positive impact of infrastructure on private capital formation. It is concluded that the continuous physical deterioration of the infrastructure stock may promote declines in the elasticity of private investment in relation to its determinants, translating into a lower sensitivity of private investment to positive shocks.